Evaluation of Cooking Methods for Reducing Nitrite Content in Ham: Evaluasi Metode Pemasakan untuk Mengurangi Kandungan Nitrit Pada Ham - Kamemura, Norio; Yoshie, Akihiro; Inubushi, Tomoko; Ono, Akari; Kudou, Mami; Yamakawa, Chiharu (Universitas Muhammadiyah Sidoarjo, 2025)
Nitrite is a common food additive used to enhance the safety and shelf life of processed meat products. However, recent concerns have emerged regarding its potential link to colorectal cancer in humans. Despite this, the effectiveness of different cooking methods in removing nitrite from processed meats remains unclear. This study aimed to identify cooking methods that effectively reduce nitrite content in ham. Three cooking methods—boiling, pan-frying, and microwave heating—were evaluated. Nitrite content in ham was measured using the diazotization-coupling reaction. The results showed that boiling significantly reduced the nitrite content in ham compared to the uncooked state. In contrast, pan-frying and microwave heating had no significant effect. Long-term storage also reduced nitrite levels, and combining storage with boiling had a synergistic effect in further reducing nitrite content. Additionally, soaking ham in condiments prior to cooking was found to be effective in lowering nitrite levels. Notably, soaking in grain vinegar resulted in a substantial reduction. Overall, the study demonstrated that boiling is an effective method for reducing nitrite content in ham. Furthermore, extended storage and pre-soaking in condiments, particularly grain vinegar, also contributed to nitrite reduction.